Posture Sensor: Cross Leg Detector at Knee Level - Leela Krishna Chand, Gudi Siva; Young Shin, Soo (EAI Endorsed Transactions on Pervasive Health and Technology, 2015)
This paper presents a wearable posture device that can detect and alert when a person tries to attempt a cross leg at the knee level. Generally having a cross leg is considered as normal but if it is done regular then it can create large number of problems such as damaging the veins, increasing the blood pressure, temporary paralysis and sometimes long term numbness. It will also help men to have good posture. The main problem is that we don’t even realize that we are doing it. So, to overcome this problem, we have developed a prototype, that can alert the user. We have developed two types of prototypes where the first one is with feedback and other one is without feedback of our activity regarding cross leg.
Keywords: wearable device; posture sensor; intel edison